The burden of gastrointestinal diseases in Japan, 1990–2019, and projections for 2035 - Yasutoshi Shiratori; Susan Hutfless; George Rateb; Katsuyuki Fukuda (JGH Open, 2023)
Abstract Background and Aim Disease burden estimation allows clinicians and policymakers to plan for future healthcare needs. Although advances have been made in gastroenterology, as Japan has an aging population, disease burden assessment is important. We aimed to report gastrointestinal disease burden in Japan since 1990 and project changes through to 2035. Methods This descriptive study examined the crude and age‐standardized rates of prevalence, mortality, and disability‐adjusted life years (DALYs) of 22 gastrointestinal diseases between 1990 and 2019. We used data from the Global Burden of Disease study 2019. We calculated the expected disease burden of gastrointestinal diseases by 2035 using an autoregressive integrated moving average. Results Since 1990, cancer has accounted for most gastrointestinal disease‐related causes of mortality and DALYs in Japan (77.1% and 71.2% in 1990, 79.2% and 73.7% in 2019, respectively). Although cancer‐associated age‐standardized mortality rates and DALYs have shown a decreasing trend, the crude rates have increased, suggesting that an aging society has a significant impact on the disease burden in Japan. Therefore, the overall gastrointestinal disease burden is expected to increase by 2035. Noncancerous chronic diseases with a high burden included cirrhosis, biliary disease, ileus, gastroesophageal reflux disorder, hernia, inflammatory bowel disease, enteric infections, and vascular intestinal disorders. In cirrhosis, the DALYs for hepatitis C decreased and the prevalence of non‐alcoholic steatohepatitis increased. Conclusion In the super‐aging Japanese society, the burden of gastrointestinal diseases is expected to increase in the coming years. Colorectal, gastric, pancreatic, and liver cancers are the focus of early detection and treatment.